Impact of one or two visits strategy on hypertension burden estimation in HYDY, a population-based cross-sectional study: implications for healthcare resource allocation decision making - Modesti, Pietro Amedeo; Rapi, Stefano; Bamoshmoosh, Mohamed; Baldereschi, Marzia; Massetti, Luciano; Padeletti, Luigi; Gensini, Gian Franco; Zhao, Dong; Al-Hidabi, Dawood; Al Goshae, Husni (BMJ Publishing Group, 2012)
Context The prevalence of hypertension in developing countries is coming closer to values found in developed countries. However, surveys usually rely on readings taken at a single visit, the option to implement the diagnosis on readings taken at multiple visits, being limited by costs. Objective To estimate more accurately the magnitude and extent of the resource that should be allocated to the prevention of hypertension. Design Population-based cross-sectional survey with triplicate blood pressure (BP) readings taken on two separate home-visits. Setting Rural and urban locations in three areas of Yemen (capital, inland and coast). Participants A nationally representative sample of the Yemen population aged 15-69?years (5063 men and 5179 women), with an overall response rate of 92% in urban and 94% in rural locations. Main outcome measure Hypertension diagnosed as systolic BP ?140?mm?Hg and/or diastolic BP ?90?mm?Hg and/or self-reported use of antihypertensive drugs. Results Hypertension prevalence (age-standardised to the WHO world population 2001) based on fulfilling the same criteria on both visits (11.3%; 95% Cl 10.7% to 11.9%), was 35% lower than estimation based on the first visit (17.3%; 16.5% to 18.0%). Advanced age, blood glucose ?7?mmol/l or proteinuria ?1+ at dipstick test at visit one were significant predictors of confirmation at visit 2. The 959 participants found to be hypertensive at visit 1 or at visit 2 only and thus excluded from the final diagnosis had a rate of proteinuria (5.0%; 3.8% to 6.5%) comparable to rates of the general population (6.1%; 5.6% to 6.6%), and of subjects normotensive at both visits (5.6%; 5.1% to 6.2%). Only 1.9% of Yemen population classified at high or very high cardiovascular (CV) risk at visit 1 moved to average, low or moderate CV risk categories after two visits. Conclusions Hypertension prevalence based on readings obtained after two visits is 35% lower than estimation based on the first visit, subjects were excluded from final diagnosis belonging to low CV risk classes.